INTEGRATED SATELLITE IMAGERY AND GEOPHYSICAL METHODS IDENTIFY LANDSLIDE SUSCEPTIBILITY ZONATION IN TABBINJAI VILLAGE, SOUTH SULAWESI - Amirin Kusmiran; Minarti Minarti; Alvia Auliya; Wahda Nur Aulia; Hasmia Hasmia; Nisrah Azizah; Arif Wijaya; Ramadhan Priadi (Indonesian Physical Review, 2026)
Tabbinjai Village is susceptible to landslides due to high rainfall, steep topography, and human activities. This study aims to determine the zone of landslide vulnerability using geophysical data and satellite imagery to generate a level of landslide vulnerability map in Tabbinjai Village. The AHP (Analytical Hierarchy Process) method is used to determine the weight composition of satellite imagery data, and Seismic vulnerability and slip plane identification are geophysical methods that include the HVSR (horizontal-to-vertical spectral ratio) method and the Wenner-Schlumberger configuration, respectively. Based on the AHP method, landslide susceptibility is classified into low (60.67%), moderate (37.89%), and high (1.44%) susceptibility zones. These spatial findings are supported by the in situ seismic vulnerability index (Kg) and geoelectrical resistivity profiles, confirming the strong likelihood of slope failure in critical areas. Therefore, integrated satellite imagery and geophysical data provide a reliable reference for regional spatial planning and disaster mitigation strategies.